Energy informatics : 4th D-A-CH Conference, EI 2015, Karlsruhe, Germany, November 12-13, 2015, Proceedings /: 4th D-A-CH Conference, EI 2015, Karlsruhe, Germany, November 12-13, 2015, Proceedings. (2015) - Unknown
No abstract available